2015
DOI: 10.1016/j.inoche.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Tuning peripheral π-stacking motifs in {Cr(tpy)2}3+ domains (tpy=2,2′:6′,2″-terpyridine)

Abstract: The homoleptic complexes [Cr (1) spectroscopic data were consistent with those reported [17]. A convenient route to homoleptic {Cr(4'-Xtpy) 2 } 3+ or heteroleptic {Cr(4'-Xtpy)(4'-Ytpy)} 3+ complexes uses a stepwise approach starting with the reaction of one equivalent of a tpy ligand with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…While the two former ions are known to be non-emissive, Cr III complexes are known to show NIR emission in the 600–800 nm region, arising from the two low-lying Cr III ( 2 E) and Cr III ( 2 T 1 ) spin–flip excited states ( Figure 13 ) (Jamieson et al, 1981 ; Kirk, 1981 , 1999 ; Forster, 1990 , 2002 ; Buldt and Wenger, 2017 ; Otto et al, 2018 ). In fact, Cr III complexes have long been known to exhibit interesting photophysical and photochemical properties as illustrated by the archetypal ter-bidentate [Cr(phen) 3 ] 3+ (Serpone et al, 1979 ; Ryu and Endicott, 1988 ; Isaacs et al, 2006 ; Donnay et al, 2007 ; Vandiver et al, 2010 ; Vasudevan et al, 2010 ; Doistau et al, 2018 , 2020 ), bis-terdentate [Cr(tpy) 2 ] 3+ (Serpone et al, 1979 ; Scarborough et al, 2012 ; Constable et al, 2014 ; Schönle et al, 2015a , b ; Barbour et al, 2017 ), and analogs (Zare et al, 2017b ; Jiménez et al, 2018 ). In all cases, the ligand-field strength induced by the phen and tpy ligands is strong enough to induce near-infrared phosphorescence arising from the lowest-lying Cr( 2 T 1 ) and Cr( 2 E) excited states, but the associated very low quantum yields (<0.2%) are strong limitations for their use as CPL probes.…”
Section: Extension Toward 3d Metal Complexes the Promising Case Of Ementioning
confidence: 99%
“…While the two former ions are known to be non-emissive, Cr III complexes are known to show NIR emission in the 600–800 nm region, arising from the two low-lying Cr III ( 2 E) and Cr III ( 2 T 1 ) spin–flip excited states ( Figure 13 ) (Jamieson et al, 1981 ; Kirk, 1981 , 1999 ; Forster, 1990 , 2002 ; Buldt and Wenger, 2017 ; Otto et al, 2018 ). In fact, Cr III complexes have long been known to exhibit interesting photophysical and photochemical properties as illustrated by the archetypal ter-bidentate [Cr(phen) 3 ] 3+ (Serpone et al, 1979 ; Ryu and Endicott, 1988 ; Isaacs et al, 2006 ; Donnay et al, 2007 ; Vandiver et al, 2010 ; Vasudevan et al, 2010 ; Doistau et al, 2018 , 2020 ), bis-terdentate [Cr(tpy) 2 ] 3+ (Serpone et al, 1979 ; Scarborough et al, 2012 ; Constable et al, 2014 ; Schönle et al, 2015a , b ; Barbour et al, 2017 ), and analogs (Zare et al, 2017b ; Jiménez et al, 2018 ). In all cases, the ligand-field strength induced by the phen and tpy ligands is strong enough to induce near-infrared phosphorescence arising from the lowest-lying Cr( 2 T 1 ) and Cr( 2 E) excited states, but the associated very low quantum yields (<0.2%) are strong limitations for their use as CPL probes.…”
Section: Extension Toward 3d Metal Complexes the Promising Case Of Ementioning
confidence: 99%
“…Creutz-Taube complex, (b) [(tpy)Ru(L)Ru(tpy)] m+ complexes, [69][70][71] (c) [(tpy)Ru II (L)Co III (tpy)] 5+ complexes displaying directional electron transfer, 72,73 (d) [(tpy)Ru II (L)Os II (tpy)] 4+ complexes displaying directional energy transfer. 74,75 six-coordinate bis-terimine 83,84 and ter-bisimine 46,81,82 Cr III complexes. Building on the identification of labile Cr III -O(triflate) bonds and their easy formation from Cr-Cl bonds, we herein propose to extend this procedure for the synthesis of a series of novel back-to-back dinuclear [X 3 Cr III (L)Cr III X 3 ] complexes (Scheme 1, X 3 = Cl 3 or X 3 = tpy), which are reminiscent of the well-known Ru II dyads.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…However, the lack of easy accessible synthetic procedures for the preparation and characterization of pure heteroleptic polynuclear chromium complexes has up to now prevented Cr III polypyridines from being used as active building blocks in (supra)molecular optical devices. Recently, Barker et al, 81 Isaacs et al 82 and Housecroft and Constable et al 46,83,84 tried to find a remedy for this frustrating limitation with the systematic exploration of the stability and lability of mononuclear 59,60 The upward green arrow stands for the lowest-energy spin-allowed absorption transition, while the downward red arrow refers to the lowest-energy phosphorescence.…”
Section: Introductionmentioning
confidence: 99%
“…15 The results indicated that the oxidation state of the Cr ions of polyCr was trivalent. From the extended X-ray absorption ne structure (EXAFS) region, the tting by using crystal structure of reported Cr complex 16 (Fig. 2b) revealed that the coordination lengths around the Cr ions Cr-N were 2.020 A and 2.208 A (R-factor; 1.37%, Table 1, EXAFS oscillation is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%